Pengaruh Earning Per Share (EPS). Return On Equity (ROE), dan Price Book Value (PBV) Terhadap Harga Saham pada perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2017 - Yosephin Windy Olyvia Siagian; Remaya Sinaga; Elisabet Sinaga; Jholant Bringg Luck Amelia Br.Sinaga (Owner : Riset dan Jurnal Akuntansi, 2020)
ABSTRACT This study is examined in order to explore how much influence Earning Per Share (EPS), Return On Equity (ROE), and Price Book Value (PBV) simultaneously and partially on stock prices on Banking Companies listed on the Indonesia Stock Exchange in 2015-2017 . This type of research used quantitative descriptive by nature sourced in the explanation stage where the research is more inclined to temperament cause or effect. The analytical method used is multiple linear regression method. The research approach used is a quantitative approach. The population quantity of 43 agencies over a total sample of 31 companies so that the total number of samples to be studied was 93 observations (31 x 3). The analysis value of the coefficient of determination is obtained from Adjusted R Square 0.942 with the intention that stock price variables can be explained in variations of EPS, ROE, and PBV variables of 94.2% while the remaining 5.8% is explained by other independent variables. The conclusions in the results of observations indicate partially EPS and PBV have a positive and significant effect on stock prices, partially ROE has a negative and significant effect on stock prices. Simultaneously, EPS, ROE and PBV have a significant effect on stock prices on Banking Companies listed on the Indonesia Stock Exchange in 2015-2017. Keywords: Earning Per Share (EPS), Return On Equity (ROE), Price Book Value (PBV), Stock Prices